2022
DOI: 10.3390/mi13101660
|View full text |Cite
|
Sign up to set email alerts
|

A Dielectric Elastomer Actuator-Driven Vibro-Impact Crawling Robot

Abstract: Over the last decade, many bio-inspired crawling robots have been proposed by adopting the principle of two-anchor crawling or anisotropic friction-based vibrational crawling. However, these robots are complicated in structure and vulnerable to contamination, which seriously limits their practical application. Therefore, a novel vibro-impact crawling robot driven by a dielectric elastomer actuator (DEA) is proposed in this paper, which attempts to address the limitations of the existing crawling robots. The no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 57 publications
0
11
0
Order By: Relevance
“…For instance, a soft robot/device can have an actual performance well below the design expectation (e.g. oscillation amplitude of the DEA in field being significantly below that in the lab tests due to resonant frequency shifts, as have been observed in the authors' previous work in [30]) or behave differently from expectation (e.g. a different resonant mode is triggered in field due to the introduced DoFs).…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…For instance, a soft robot/device can have an actual performance well below the design expectation (e.g. oscillation amplitude of the DEA in field being significantly below that in the lab tests due to resonant frequency shifts, as have been observed in the authors' previous work in [30]) or behave differently from expectation (e.g. a different resonant mode is triggered in field due to the introduced DoFs).…”
Section: Introductionmentioning
confidence: 84%
“…This is due to that, despite that the other motion modes of the cone DEAs can be utilized in novel applications such as acoustic devices [22], the majority of research focuses on the first mode (i.e. vertical translation considered in this work) which exert the highest stroke and power outputs for soft robotic locomotion [7,30] or highperformance miniature soft pumps [25,28]. The equations of motion for this two-DoF system are developed in the rest of this subsection where the nonlinear dynamic model for the double cone DEA (m 1 ) applies to both cases while the equation of motion for the compliant support (m 2 ) in two cases will be given separately.…”
Section: Nonlinear Dynamic Model Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly to the push-pull DEA, the double conical actuation design integrates two conical DEA back-to-back via rigid support or magnets [ 28 , 29 ]. Bionic vehicles [ 30 ], binary actuation [ 31 ], and pipeline robots [ 32 ] have been implemented in a double conical actuator. Theoretical and experimental studies have been conducted to evaluate the actuation performance of conical DEAs, as reported in references [ 22 , 23 , 33 , 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, utilizing a vibro-impact mechanism and a DEA, we proposed a soft actuatorbased resonant-impact DEA system in our previous study [37]. This system mainly consists of a resonant DEA and an elastic constraint as the output to any payloads.…”
Section: Introductionmentioning
confidence: 99%